Thermal self-oscillations in monolayer graphene coupled to a superconducting microwave cavity. (1st October 2022) - Haque, M T; Will, M; Zyuzin, A; Golubev, D; Hakonen, P
Abstract: Nonlinear phenomena in superconducting resonator circuits are of great significance in the field of quantum technology. We observe thermal self-oscillations in a monolayer graphene flake coupled to molybdenum–rhenium superconducting resonator. The graphene flake forms a SINIS junction coupled to the resonator with strong temperature dependent resistance. In certain conditions of pump power and frequency, this nonlinearity leads to thermal self-oscillations appearing as sidebands in cavity transmission measurements with strong temperature dependence and gate tunability. The experimental observations fit well with theoretical model based on thermal instability. The modelling of the oscillation sidebands provides a method to evaluate electron phonon coupling in disordered graphene sample at low energies.